POTRET PENURUNAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH AB: STUDI INTERPRETIF - Rahmat Zuhdi (InFestasi, 2013)
This study is based on the phenomenon of decline in opinion of districts/municipalities financial statement in East Java, especially AB local government financial statement as the only local government financial statement in East Java who is predicated as unqualified opinion in 2006, and then deteriorated in 2007, 2008, and 2009 continously-also got adverse opinion, disclaimer, and adverse opinion. The purpose of this study is to reveals the reasons of the phenomenon of decline in the quality of AB local government financial statement. This study uses a phenomenological approach. Data were collected from in-depth interviews with informants, and then analyzed using a model of Creswell.The results showed that (1) the application of financial information system of AB local government has not been integrated so that caused data assets are not well documented, (2) AB local government has not maximize efforts to improve the quality of human resources who have the capability of accounting, (3) the differences in policy between the Ministry of Health and Ministry of the Domestic Affairs caused local government disagree with each other in interpreting the policy, so that each local government use different policies in managing the fund of health insurance in the region.